Respostas

2014-01-17T14:18:53-02:00
(X+10).(x+10)=x² + (x+5). (x+5)
x²+10x+10x+100= x²+x²+5x+5x+25
 x²+20x+100-2x²-10x-25=0
-x²+10x+75=0

a= -1 b= 10 c= 75
Δ= (10)²-4·(-1)·75
Δ= 100- (-300)
Δ= 100+300
Δ= 400

x= -b+/- 
√Δ/2a
x= -10+/-√400/2.(-1)
x= -10+/-20/-2
x'= -5
x''=+15

S:[-5,15]
A melhor resposta!
2014-01-17T14:35:47-02:00
(x + 10) . (x + 10) = x² + (x + 5) . (x + 5)
x² + 10x + 10x + 100 = x² + x² + 5x + 5x + 25
x² + 20x + 100 = 2x² + 10x + 25
x² - 2x² + 20x - 10x + 100 - 25 = 0
- x² + 10x + 75 = 0

a = - 1                  b = 10               c = 75
Δ = b² - 4 . a . c
Δ = 10² - 4 (- 1) * 75
Δ = 100 + 300
Δ = 400

x = - b ± √Δ
     ---------------
         2 . a
x = - 10 ± √400
    ---------------------
           2 (- 1)
x = - 10 ± 20
     ----------------
          - 2
x' = - 10 + 20 
          - 2
x' = 10 
÷ (- 2)
x' = - 5

x" = - 10 - 20 
          - 2
x" = - 30 ÷ (- 2)
x" = 15

Resposta: {- 5; 15}
1 5 1
Vlw mesmo Fernando! Abraço!
Eu que agradeço
;D